Progressive Host-Directed Strategies to Potentiate BCG Vaccination Against Tuberculosis - Negi, Kriti; Bhaskar, Ashima; Dwivedi, Ved Prakash (Frontiers in Immunology, 2022)
The pursuit to improve the TB control program comprising one approved vaccine, M. bovis Bacille Calmette-Guerin (BCG) has directed researchers to explore progressive approaches to halt the eternal TB pandemic. Mycobacterium tuberculosis (M.tb) was first identified as the causative agent of TB in 1882 by Dr. Robert Koch. However, TB has plagued living beings since ancient times and continues to endure as an eternal scourge ravaging even with existing chemoprophylaxis and preventive therapy. We have scientifically come a long way since then, but despite accessibility to the standard antimycobacterial antibiotics and prophylactic vaccine, almost one-fourth of humankind is infected latently with M.tb. Existing therapeutics fail to control TB, due to the upsurge of drug-resistant strains and increasing incidents of co-infections in immune-compromised individuals. Unresponsiveness to established antibiotics leaves patients with no therapeutic possibilities. Hence the search for an efficacious TB immunization strategy is a global health priority. Researchers are paving the course for efficient vaccination strategies with the radically advanced operation of core principles of protective immune responses against M.tb. In this review; we have reassessed the progression of the TB vaccination program comprising BCG immunization in children and potential stratagems to reinforce BCG-induced protection in adults.